Sperm meiotic segregation of a balanced interchromosomal reciprocal insertion resulting in recurrent spontaneous miscarriage. Issue 1 (July 2018) - Salaun, Gaëlle; Tchirkov, Andrei; Francannet, Christine; Pons, Hanae; Brugnon, Florence; Pebrel-Richard, Celine; Gouas, Laetitia; Eymard-Pierre, Eleonore; Vago, Philippe; Goumy, Carole
Abstract: Research question: Is sperm fluorescence in-situ hybridization (FISH) useful to evaluate the risk of chromosomally unbalanced gametes in interchromosomal reciprocal insertion (IRI) carriers? How do these imbalances lead to recurrent miscarriages? Design: This study reports a clinical and molecular study of a rare familial balanced IRI resulting in recurrent spontaneous miscarriage. Sperm FISH was performed to estimate the number of unbalanced gametes. Results: A 31-year-old healthy male (proband) and his 28-year-old female partner were referred to the Genetics Department for three spontaneous miscarriages occurring during the first trimester of pregnancy. FISH analysis of the proband with the LSI TRA/D (14q11.2) and DiGeorge N25 (22q11.2) break-apart probes showed the presence of a balanced IRI between 14q11.2 and 22q11.2 chromosomal regions. This IRI was also identified in the proband's father. Sperm FISH with the same probes showed that more than 40% of gametes of the proband were unbalanced for either 14q11.2 or 22q11.2, despite normal sperm parameters. FISH analysis of a product of conception indicated that unbalanced gametes result in a non-viable fetus. Conclusions: This study shows the value of sperm FISH analysis in improving genetic reproductive advice for IRI carriers. Disruption of critical genes through this rearrangement and their consequent functional impairment could result in recurrent miscarriages. In this case, several genes located in the 14q11.2 region, particularly RNase 3, would be good candidates to explain the lethality of the imbalances.